An Injectable Asymmetric‐Adhesive Hydrogel as a GATA6+ Cavity Macrophage Trap to Prevent the Formation of Postoperative Adhesions after Minimally Invasive Surgery. (18th November 2021) - Wu, Xiaoqi; Guo, Weihong; Wang, Ling; Xu, Yichao; Wang, Zihan; Yang, Yang; Yu, Liu; Huang, Junfei; Li, Yanbin; Zhang, Hongwu; Wu, Yaobin; Li, Guoxin; et al.
Abstract: Antiadhesive hydrogels have been developed for preventing the formation of postoperative adhesions. However, it is challenging to design an injectable hydrogel with superior tissue retention properties that can be easily administered during minimally invasive surgical procedures to prevent the development of postsurgical adhesions. In this study, an injectable asymmetric‐adhesive hydrogel is fabricated using photocurable catechol‐grafted hyaluronic acid (HAD) for use during minimally invasive procedures to prevent the development of postoperative adhesions. The hydrogel exhibits superior tissue retention properties and favorably inhibits postoperative adhesion formation. This is the first time that an injectable hydrogel is designed via photocrosslinking to control asymmetric‐adhesive capability. The results show that laparoscopically delivered HAD precursor acts as a wet adhesive on the injured cecum, while its outward‐facing side is nonadherent after photocrosslinking. Intriguingly, the HAD acts as a physical barrier and polyanion trap to neutralize scavenger receptors, thereby inhibiting collagen deposition and uncontrolled recruitment of GATA6 + cavity macrophages. Furthermore, the HAD significantly downregulates the expression of fibrosis‐related and proinflammatory cytokines and promotes macrophage polarization. These results demonstrate that injection of the hydrogel can be readily integrated into laparoscopic surgery. Moreover, the HAD may be suitable for preventing adhesion formation after minimally invasive surgical procedures. Abstract : An injectable asymmetric‐adhesive hydrogel based on the photocurable catechol‐grafted hyaluronic acid is developed to prevent the development of postoperative adhesions during a minimally invasive procedure. Moreover, this hydrogel acts as a polyanion trap to neutralize scavenger receptors, thereby inhibiting the uncontrolled recruitment of GATA6+ cavity macrophages and collagen deposition.